Повышение эффективности использования газа на компрессорных станциях - Динков В. А. Василий Александрович; Гриценко А. И. Александр Иванович; Васильев Ю. Н. Юрий Николаевич; Мужиливский П. М. Петр Михайлович (Москва, Недра, 1981)
Авт. указ. на обороте тит. л.